2015
DOI: 10.1007/s10198-015-0686-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of ICT on innovation and performance of European hospitals: an exploratory study

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In a study of firms drawn from 11 OECD countries, Spiezia ( 2011 ) finds that firms with higher intensity of IT use are more innovative, especially in product and marketing innovation. This is consistent with Arvanitis and Loukis' ( 2016 ) study of 743 hospitals in 18 European countries in which IT applications such as use in patient administration and medical record have a positive effect on product and process innovation. In a study of 288 firms in Mexico, Cuevas-vargas et al ( 2016 ) demonstrate that there is a positive and significant relationship between IT applications and product, process and organisational innovation.…”
Section: Review Of Literaturesupporting
confidence: 90%
“…In a study of firms drawn from 11 OECD countries, Spiezia ( 2011 ) finds that firms with higher intensity of IT use are more innovative, especially in product and marketing innovation. This is consistent with Arvanitis and Loukis' ( 2016 ) study of 743 hospitals in 18 European countries in which IT applications such as use in patient administration and medical record have a positive effect on product and process innovation. In a study of 288 firms in Mexico, Cuevas-vargas et al ( 2016 ) demonstrate that there is a positive and significant relationship between IT applications and product, process and organisational innovation.…”
Section: Review Of Literaturesupporting
confidence: 90%
“…Many scholars have shown that the benefits of using ICT are closely linked to the expression of factors inside the organizational employees who use them (Sarayani et al, 2014). Arvanitis and Loukis (2016) provide empirical evidence of the positive influence of ICT, human capital, and new organizational practices on workplace productivity in Greece and Switzerland. Black and Lynch (2001) investigate the influence of information technology, human resource management practices, and business reorganization on productivity.…”
Section: Complementarity Theorymentioning
confidence: 99%
“…Despite the Internet's massive impact on all areas of life and the digital economy's increasingly important role in global markets, systematic studies of the digital economy's impact on entrepreneurship are scarce. Scholars have elaborated on the impact of digital technology on economic performance in terms of growth (Abendin & Duan, 2021;Murthy et al, 2021;Twumasi et al, 2021), innovation (Arvanitis & Loukis, 2016;Jun et al, 2021), financial inclusion (Arner et al, 2020;Ozili, 2018), household consumption (Wan et al, 2021), and poverty reduction (Kelikume, 2021;Ozili, 2020). However, the extant literature has failed to achieve a consensus on whether digital technologies can stimulate entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%